Nasal Mucociliary Clearance in Smokers: A Systematic Review - Prasetyo,Awal (2021)
Abstract Introduction Smoking is one of the most important causes of mortality and morbidity in the world, as it is related to the risk factor and etiology of respiratory-tract diseases. Long-term smoking causes both structural and functional damage in the respiratory airways, leading to changes in nasal mucociliary clearance (NMC). Objectives The aim of the present study was to look systematically into the current literature and carefully collect and analyze results to explore NMC in smokers. Data Synthesis Two independent reviewers conducted a literature search on some Electronic database: Pubmed, Medline, Ebsco, Springer Link, Science Direct, Scopus, and Proquest searching for articles fulfilling the inclusion and exclusion criteria. The lead author independently assessed the risk of bias of each of the included studies and discussed their assessments with the other two authors to achieve consensus. Of the 1,654 articles identified in the database search, 16 met the criteria for this review. Most of the articles (15 out of 16) showed the impairment of NMC in smokers. Conclusion The present systematic review suggests that there is an impairment of NMC in smokers. The impairment is not only observed in cigarette smoking, but also in passive smoking, bidi smoking, electronic smoking, and hookah smoking. The impairment of NMC in chronic exposure to smoking is caused by the ciliotoxic effect, hypersecretion and viscoelastic change of mucous, airway surface liquid depletion, increased oxidative stress, and deteriorations in the inflammatory and immune systems.